2016
DOI: 10.1159/000442671
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Morphological Changes in the CNV Net after Intravitreal Anti-VEGF Evaluated with OCT Angiography

Abstract: Purpose: To assess and describe sequential morphological changes in the choroidal neovascularization (CNV) net using optical coherence tomography angiography (OCTA) in patients undergoing treatment with intravitreal antivascular endothelial growth factor (VEGF). Methods: Prospective cohort study. OCTA was performed sequentially: before (t0), 1 h (t1), 1 week (t2) and 1 month after the injection (t3), using Avanti RTVue XR equipped with the AngioVue® software (Optovue, Calif., USA). All images were classified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
3
11
0
1
Order By: Relevance
“…Several groups have characterised the anatomy of small vessels and proposed methods to classify choroidal neovascularisation based on these features . OCT‐A has also shown the shrinkage of choroidal neovascularisation after injection with anti‐vascular endothelial growth factor (anti‐VEGF) agents . By examining the sequential morphological changes of small vessels, the OCT‐A may be a powerful tool, particularly in the diagnosis and monitoring of choroidal neovascularisation, and characterising the treatment response to intra‐vitreal anti‐VEGF injections.…”
Section: Applications In Retinal Diseasementioning
confidence: 99%
“…Several groups have characterised the anatomy of small vessels and proposed methods to classify choroidal neovascularisation based on these features . OCT‐A has also shown the shrinkage of choroidal neovascularisation after injection with anti‐vascular endothelial growth factor (anti‐VEGF) agents . By examining the sequential morphological changes of small vessels, the OCT‐A may be a powerful tool, particularly in the diagnosis and monitoring of choroidal neovascularisation, and characterising the treatment response to intra‐vitreal anti‐VEGF injections.…”
Section: Applications In Retinal Diseasementioning
confidence: 99%
“…26 OCTA can be used to monitor CNV after anti-vascular endothelial growth factor (anti-VEGF) treatment with reduced CNV density and size, vascular rarefication, and loss of smaller or peripheral capillaries after therapy. [27][28][29][30][31] Flow within a vascular network may be apparent on OCTA in a disciform scar from AMD. 32 One study demonstrated alterations in the retinal vasculature in early to intermediate AMD with reduced vessel density in both the superficial and deep inner retinal plexuses and reduced choroidal thickness compared with control.…”
Section: Age-related Macular Degeneration and Choroidal Neovascularizmentioning
confidence: 99%
“…On FA it can be difficult to distinguish between a low‐grade leakage caused by CNV activity and staining or window defects unrelated to neovascular activity . OCT‐A, in contrast, visualizes neovascular networks, while phenomena such as leakage or pooling indicative for neovascular activity are not displayed …”
Section: Introductionmentioning
confidence: 99%
“…6 OCT-A, in contrast, visualizes neovascular networks, while phenomena such as leakage or pooling indicative for neovascular activity are not displayed. 6,[21][22][23][24] In this study, we compared the accuracy of OCT, FA and OCT-A to detect active neovascularization in PXE. Even though all three imaging techniques are employed in daily practice, a systematic comparison of these for more complex fundus pathologies is lacking.…”
Section: Introductionmentioning
confidence: 99%